"I Will Speak in Their Own Language": Yugoslav Socialist Monuments and Science Fiction. Issue 3 (December 2019) - Isto, Raino
Abstract : This article analyzes the relationship between science fiction paradigms and socialist-era Yugoslav monuments through a discussion of two recent independent films, Sankofa and A Second World . In Sankofa, these monuments are documented as part of the creation of a final collective archive before the apocalyptic destruction of human society, while in A Second World the monuments visually narrate the story of an elderly man who claims to be communicating with an alien utopia. The article considers the historical context of these monuments, how they emerged into popular culture, and how their association with science fiction affects our understandings of them.